Perception and adaptation of coffee producers to climate change in Puebla and Oaxaca, Mexico - Jaramillo-Villanueva, José Luis; Guerrero-Carrera, Jesus; Vargas-López, Samuel; Bustamante-González, Ángel (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of this research was to analyze the explanatory factors of the perception and adaptation of coffee producers to climate change in the Mazateca Oaxaca and Cuetzalan Puebla regions. The information was gathered from a survey of coffee producers, which included questions about producer sociodemographic characteristics, use of agricultural technology, costs and income, perception, adaptation and effects on coffee cultivation due to climate change. Simple random sampling was applied, with 95% reliability and 10% precision. The producers identified that climate change is affecting the yield and quality of the coffee grain. The perception of risk is significantly correlated (p < 0.05) with measures of adaptation to climate change. The explanatory factors of the perception that were significant (p < 0.05) are receiving technical assistance, high schooling, high household income, size of more than 2.0 ha of the plantation and having had effects due to changes in the climate variables in the last five years. Receiving technical assistance versus not receiving it, and having high education versus low education increased the logarithm of the odds ratio by 0.82 and 0.61 respectively. Having a high income increased the probability of making adaptations (66%). Coffee growers have a strong perception of climatic changes and their impact on coffee agroecosystems. A significant correlation was found between perception and adaptations to climate change.